Perlindungan Hukum Bagi Karya Fotografi Ditinjau Dari Undang-Undang Hak Cipta (Studi Kasus Putusan Pengadilan Negeri Surabaya Nomor: 10/HKI/Hak Cipta/2014/PN. Niaga Sby) - Satria Perdana; O.K Saidin; T. Keizerina Devi Azwar; Jelly Leviza (Iuris Studia: Jurnal Kajian Hukum, 2021)
Portraiture is one of the art of photography by displaying human objects either individually or in groups, which emphasizes the personality elements of the photo object. According to Article 1 Number 10 of Law Number 28 of 2014 concerning Copyright, it is explained that a portrait is a photographic work with a human object. The formulation of the problem in this thesis is how actions can be categorized as commercialization of photographic works without permission, what are the legal provisions regarding the settlement of copyright disputes in the case of commercialization of photographic works without permission, how are the judges' legal considerations in the decision Number 10/HKI/Hakcopy/2014 /PN.Sby in terms of Law Number 28 of 2014 concerning Copyright. Acts that can be categorized as commercialization of photographic works without permission are commercial use, reproduction, announcements, distribution or communication of the portraits made for the purposes of commercial advertisements or advertising without the written consent of the person being photographed or his heirs. Legal provisions regarding the settlement of copyright disputes in the event of commercialization of photographic works without permission can be reached through litigation dispute resolution, namely settlement through a court institution. In addition, non-litigation dispute resolution efforts can also be taken, namely dispute resolution outside the court, such as through alternative dispute resolution or arbitration. The judge's legal considerations in the decision Number 10/HKI/Copyright/2014/PN.Sby are appropriate in terms of Law Number 28 of 2014 concerning Copyright, namely the defendant without the Plaintiff's approval has used the image/photo published in the Java Post print daily so that it is true that the Defendant violated the plaintiff's copyright as referred to in the provisions of Article 12 paragraph (1) of Law Number 28 of 2004 concerning Copyright. Therefore, the legal consequences arising from the use of portraits without permission are compensation for those who feel aggrieved. This is stated in Article 96 paragraph (1), paragraph (2), and paragraph (3) which is strengthened by Article 99 (1), paragraph (2), and paragraph (3) letters c and d, as well as Article 115